Cytokines as inducers of postperfusion systemic inflammatory reaction in cardiosurgical patients with different duration of coronary pathology - S. P. Chumakova; O. I. Urazova; V. M. Shipulin; V. V. Novitsky; S. A. Khardikova (Бюллетень сибирской медицины, 2018)
Aim. The changes of blood cytokine profile in patients with ischemic heart disease (IHD) with different development rates and formation of systemic inflammatory response (SIR) after coronary artery bypass grafting by using cardiopulmonary bypass (CPB) are analyzed in this article.Materials and methods. The patients with slowly progressive of IHD (20 patients) and rapidly progressive of IHD (20 patients) were examined. The concentration of interleukine (IL) 1β, IL-1ra, IL-4, IL-6, IL-8 and tumor necrosis factor (TNF) α in blood plasma were evaluated by ELISA at patients with IHD before surgery and at 6 and 24 h after surgery.The results of the study showed that concentration of IL-1β, IL-6, IL-8, TNF-α and IL-1ra in blood plasma increases in patients with IHD of both groups before surgery. The concentration of IL-4 in the blood saved in the normal range before the operation in the case of slow disease progression, but maximum increase in content of proinflammatory (TNF-α, IL-6) and anti-inflammatory (IL-4, IL-1ra) cytokines in the blood and the IL-1ra/IL-1β ratio was detected in a rapidly developing of IHD. It was noticed that after coronary artery bypass grafting in patients with long history case of IHD the content of IL-1β, IL-8, TNF-α, IL-1ra, IL-4 increased with a normalization of the IL-6 concentration in the blood; in patients with a short period of IHD increase of IL-1 concentration and high content of IL-6 are combined with remaining unchanged level of IL1β, IL-8, IL-4 and negative dynamics of the TNF-α concentration in the blood. Thus, the operation in the СРВ in the case of IHD with prolonged course induces the formation of SIR, typical for acute inflammation, and coordinated anti-inflammatory response, and in the case of short period of coronary disease progress this operation causes SIR, characteristic for chronic inflammation, and uncoordinated anti-inflammatory response.